Intelligent Transportation Decision Analysis System Based on Big Data Mining. Issue 3 (February 2019) - Liao, Huichuan
Abstract: In the big data era, the intelligent transportation field also has begun to use big data technology to mine and analyze the massive traffic data, from which to extract valuable data information, for people to travel to provide convenience and for the relevant traffic decisions to provide an important basis. This paper mainly describes the intelligent transportation and big data mining, and analyzes the application of big data and data mining technology in intelligent transportation decision analysis system, which provides a new way to improve traffic congestion and relieve traffic pressure in big data era.